(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
The article presents materials illustrating the current state of pension provision in a number of countries around the world, starting with the countries with the highest per capita incomes and ending with the countries with the lowest incomes. Variants of modeling pension systems in different countries are analyzed. The article provides an analysis of current global trends in the development of pension systems.